The Social Construction of Generation Z Adolescents Regarding Mothers’ Roles as Primary Family Breadwinners - Allifia Fatika Putri; Tri Marhaeni Pudji Astuti (JESS (Journal of Educational Social Studies), 2026)
Changes in family structure in Indonesia have shifted gender role divisions, including the increasing number of mothers serving as primary breadwinners. However, how Generation Z adolescents interpret this change remains underexplored, despite their critical stage of identity formation, openness to gender equality, and exposure to social and digital influences shaping family perspectives. This study aims to examine the social construction of Generation Z adolescents regarding mothers’ roles as primary breadwinners by considering personal experiences, family interactions, and socioeconomic backgrounds. Employing a qualitative phenomenological approach, the study involved six adolescents aged 18–21 from upper, middle, and lower economic classes. Data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic analysis. The findings reveal that socioeconomic class shapes each stage of adolescents’ social construction, from externalization and objectivation to internalization. Upper-class adolescents perceive working mothers as a conscious choice and self-actualization, middle-class adolescents view it as family negotiation and cooperation, while lower-class adolescents regard it as an economic necessity and a form of family resilience. Academically, this study contributes to family and gender sociology from a cross-class adolescent perspective. Practically, the findings inform educators, communities, and policymakers in strengthening gender literacy, social studies education, and contextsensitive family empowerment programs.